Early standardized clinical judgement for syncope diagnosis in the emergency department. (23rd March 2021) - du Fay de Lavallaz, J.; Badertscher, P.; Zimmermann, T.; Nestelberger, T.; Walter, J.; Strebel, I.; Coelho, C.; Miró, Ò.; Salgado, E.; Christ, M.; Geigy, N.; Cullen, L.; et al.
Abstract: Background: The diagnosis of cardiac syncope remains a challenge in the emergency department (ED). Objective: Assessing the diagnostic accuracy of the early standardized clinical judgement (ESCJ) including a standardized syncope‐specific case report form (CRF) in comparison with a recommended multivariable diagnostic score. Methods: In a prospective international observational multicentre study, diagnostic accuracy for cardiac syncope of ESCJ by the ED physician amongst patients ≥ 40 years presenting with syncope to the ED was directly compared with that of the Evaluation of Guidelines in Syncope Study (EGSYS) diagnostic score. Cardiac syncope was centrally adjudicated independently of the ESCJ or conducted workup by two ED specialists based on all information available up to 1‐year follow‐up. Secondary aims included direct comparison with high‐sensitivity cardiac troponin I (hs‐cTnI) and B‐type natriuretic peptide (BNP) concentrations and a Lasso regression to identify variables contributing most to ESCJ. Results: Cardiac syncope was adjudicated in 252/1494 patients (15.2%). The diagnostic accuracy of ESCJ for cardiac syncope as quantified by the area under the curve (AUC) was 0.87 (95% CI: 0.84–0.89), and higher compared with the EGSYS diagnostic score (0.73 (95% CI: 0.70–0.76)), hs‐cTnI (0.77 (95% CI: 0.73–0.80)) and BNP (0.77 (95% CI: 0.74–0.80)), all P  < 0.001. Both biomarkers (alone or in combination) on top of the ESCJ significantly improved diagnostic accuracy. Conclusion: ESCJ including a standardized syncope‐specific CRF has very high diagnostic accuracy and outperforms the EGSYS score, hs‐cTnI and BNP. Abstract :